2013
DOI: 10.4244/eijv9i5a98
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated balloons for de novo coronary lesions: results from the Valentines II trial

Abstract: The Valentines II trial demonstrates the feasibility of using a second-generation DIOR DCB as adjunct to POBA in de novo coronary lesions. This approach achieved high procedural success with acceptable rates of bail-out stenting and low MACE rates at mid-term follow-up, and offers an attractive alternative for revascularisation of patients who are unsuitable candidates for drug-eluting stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 25 publications
7
65
1
1
Order By: Relevance
“…7,8) In contrast, for de novo coronary artery lesions, no definite evidence supporting the superiority of DCB over DES is available, 17,18) while a few registries have shown acceptable results regarding the safety and efficacy of DCB in de novo coronary lesions. 19,20) In the Valentines II, a prospective registry of 109 lesions in 103 patients with stable or unstable angina and/or positive stress test with de novo lesions of > 50% stenosis undergoing plain old balloon angioplasty followed by DCB dilation, the primary endpoint of major adverse cardiac events at 8 months was 8.7% with 1% all-cause death, 1% myocardial infarction, and 2.9% target lesion revascularization (TLR), despite the 11.9% bail-out bare metal stent (BMS) implantation. 19) In part of the SeQuent Please World Wide Registry, a prospective registry of 554 lesions in 496 patients with de novo lesions (small vessels with a mean reference diameter of 2.6 mm) undergoing DCB dilation alone or DCB dilation followed by BMS implantation, the primary endpoint of clinically driven TLR at 9 months was 1.0% in DCB alone and 2.4% in DCB/BMS with 0.7%/0.0% MI and 1.0%/1.2% cardiac death, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) In contrast, for de novo coronary artery lesions, no definite evidence supporting the superiority of DCB over DES is available, 17,18) while a few registries have shown acceptable results regarding the safety and efficacy of DCB in de novo coronary lesions. 19,20) In the Valentines II, a prospective registry of 109 lesions in 103 patients with stable or unstable angina and/or positive stress test with de novo lesions of > 50% stenosis undergoing plain old balloon angioplasty followed by DCB dilation, the primary endpoint of major adverse cardiac events at 8 months was 8.7% with 1% all-cause death, 1% myocardial infarction, and 2.9% target lesion revascularization (TLR), despite the 11.9% bail-out bare metal stent (BMS) implantation. 19) In part of the SeQuent Please World Wide Registry, a prospective registry of 554 lesions in 496 patients with de novo lesions (small vessels with a mean reference diameter of 2.6 mm) undergoing DCB dilation alone or DCB dilation followed by BMS implantation, the primary endpoint of clinically driven TLR at 9 months was 1.0% in DCB alone and 2.4% in DCB/BMS with 0.7%/0.0% MI and 1.0%/1.2% cardiac death, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…19,20) In the Valentines II, a prospective registry of 109 lesions in 103 patients with stable or unstable angina and/or positive stress test with de novo lesions of > 50% stenosis undergoing plain old balloon angioplasty followed by DCB dilation, the primary endpoint of major adverse cardiac events at 8 months was 8.7% with 1% all-cause death, 1% myocardial infarction, and 2.9% target lesion revascularization (TLR), despite the 11.9% bail-out bare metal stent (BMS) implantation. 19) In part of the SeQuent Please World Wide Registry, a prospective registry of 554 lesions in 496 patients with de novo lesions (small vessels with a mean reference diameter of 2.6 mm) undergoing DCB dilation alone or DCB dilation followed by BMS implantation, the primary endpoint of clinically driven TLR at 9 months was 1.0% in DCB alone and 2.4% in DCB/BMS with 0.7%/0.0% MI and 1.0%/1.2% cardiac death, respectively. 20) Although the role of DCB in de novo coronary artery lesions including post-rotational atherectomy lesions remains unclear, it is reasonable to propose that DCB-based PCI could be an alternative revascularization therapy of choice among patients with de novo coronary lesions who are inappropriate candidates for DES implantation.…”
Section: Discussionmentioning
confidence: 99%
“…DEB je korišten u 28 bolesnika (11,3% svih indikacija) na krvnoj žili >2,8 mm. Pregledom literature, do sada je objavljeno jedno istraživanje na de novo lezijama ≥2,5 mm, bez ograničenja maskimalnoga promjera krvne žile u uključnim kriterijima -The Valentines II trial 10 . Rezultati na 103 bolesnika su pokazali da je postupak siguran (2% smrti i infarkta miokarda) te efikasan (6,9% revaskularizacije ciljne lezije i ciljne krvne žile) tijekom 227 ± 40 dana praćenja.…”
Section: Raspravaunclassified
“…DEB was used on 28 patients (11.3% of all indications) on a blood vessel >2.8 mm. by reviewing the literature, up-to-date there has been one research conducted on de novo lesions ≥2.5 mm, without the limit on the maximum diameter of the blood vessel in the crucial criteria -The Valentines II trial 10 . The results on 103 patients have shown that the procedure is safe (2% of deaths and myocardial infarctions) and efficient (6.9% target lesion and target blood vessel revascularization) over the span of 227 ± 40 days of observation.…”
Section: Raspravamentioning
confidence: 99%
“…However, clinical information on the efficacy and safety in de novo coronary lesions is limited. Moreover, several studies and trials have produced conflicting results in patients with a stable coronary artery disease [8,9,10,11,12,13]. Therefore, we hypothesize that DEB may also be safe for the treatment of non-small coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%